Despite Recovery from Necrotizing Enterocolitis Infants Retain a Hyperinflammatory Response to Injury - Snyder KB; Calkins CL; Golubkova A; Leiva T; Schlegel C; Hunter CJ (Dove Medical Press, 2024)
Katherine B Snyder,1,2 Chase L Calkins,3 Alena Golubkova,1,2 Tyler Leiva,1,2 Camille Schlegel,1 Catherine J Hunter1,2 1Division of Pediatric Surgery, Oklahoma City, OK, 73104, USA; 2Department of Surgery, The University of Oklahoma Health Sciences Center, Oklahoma City, OK, 73104, USA; 3College of Medicine, The University of Oklahoma College of Medicine, Oklahoma City, OK, 73104, USACorrespondence: Catherine J Hunter, Department of Pediatric Surgery, Oklahoma Children's Hospital, 1200 Everett Drive, ET NP 2320, Oklahoma City, OK, 73104, USA, Email catherine-hunter@ouhsc.eduBackground: Necrotizing enterocolitis (NEC) is the leading gastrointestinal cause of death of premature neonates. NEC is associated with prematurity, a hyperinflammatory response, and dysregulation of intestinal barrier function. We hypothesize that patients with NEC will have, and continue to have after recovery, an increased hyperinflammatory intestinal response compared to those patients without NEC.Methods: Neonates with NEC, those that have recovered from NEC, and those without NEC undergoing intestinal resections had specimens collected and snap frozen or generated into enteroids. The enteroids were treated with 100ug/mL lipopolysaccharide (LPS) and subjected to 24 hr of hypoxia together, then compared with untreated controls. Expression of Tumor Necrosis Factor (TNF-α) and interleukin 8 (IL-8) were evaluated via RT-qPCR and ELISA to measure inflammatory response. ANOVA determined statistical significance (p< 0.05).Results: There was no difference in inflammatory markers in recovered NEC tissue compared to non-NEC tissue on RTqPCR (p=0.701 TNF-α and 0.861 IL-8). However, recovered NEC enteroids demonstrate elevated levels of inflammatory markers after treatment compared to non-NEC enteroids after treatment on RTqPCR (p=0.0485 TNF-α, p=0.0057 IL-8) and ELISA (p=0.0354 TNF-α, p=0.0011 IL-8). Recovered NEC enteroids that underwent treatment demonstrated increased inflammatory markers compared to recovered NEC enteroids without treatment on RTqPCR (p=0.0045 TNF-α, p=0.0002 IL-8) and ELISA (p=0.034 TNF-α, p=0.0002 IL-8) suggesting a heightened inflammatory response to a second hit.Conclusion: Intestinal tissue resected from neonates with NEC has an elevated hyperinflammatory response compared to neonates recovered from NEC and neonates without NEC. Enteroids generated from patients that have recovered from NEC have a heightened inflammatory response in response to NEC inducing stimuli compared to controls. This tendency towards an increased hyperinflammatory state may be correlated with an infant's proclivity to develop NEC and demonstrates the significance of a second hit on this tissue creating a heightened inflammatory response. This could be correlated with the impact and trajectory of an illness post recovery from NEC.Keywords: necrotizing enterocolitis, recovery, hyperinflammatory, enteroids